A Review on Hancerli Hikaye-i Garibesi, Intibah and Zehra - Seda İzmirli Karamanlı (Akademik Dil ve Edebiyat Dergisi, 2026)
This article examines the frame of rewriting practice, which I applied on novels of Namık Kemal’s İntibah (Awakening), Nabizâde Nâzım’s Zehra (Zehra) and an anonymous folktale Hançerli Hikâye-i Garîbesi (The Strange Story of the One with the Dagger) together. This paper explains how ambivalent narrator positions are sustained and how the “liminality” of these works can be evaluated with the help of close reading practice on these texts. I will expose that the relationship among Hançerli Hikâye-i Garîbesi, İntibah and Zehra is based on the concept of a “creative imitation” in accordance with the expectations of the historical addressee under the influence of social, political and historical circumstances in the Ottoman Empire. I will position “the reader” as the person who is expected to understand and expound the text according to his own background. And, I will interpret the intervening narrator as the one who meets the expectations of the historical addressee of the Ottoman society and who serves anti-adultery propaganda. I will demonstrate that in the texts in which the elements of preternaturalness and comedy are gradually disappearing and the signs of realism are increasingly strengthened, there is an ambivalent narration which is neither fully rooted in tradition nor in romanesque realism.